The Relationship between Knowledge and Anxiety Levels of Midwives in Providing Delivery Assistance in the Era of the Covid-19 Pandemic At Upt Health Center Seibamban Kec. Batang Serangan Langkat Regency in 2021 - Muslimah Pase (Institute of Computer Science (IOCS), 2022)
Breast tumor is one type of tumor found in the breast and most often attacks women. Based on a report from the New South Wales Breast Center Institute in the United States, Fibroadenoma mammae usually occurs in adolescent girls, namely at the age of 21-25 years. Less than 5% of Fibroadenoma mammae occurs at the age above 50 years and the prevalence is more than 29% of women affected by Fibroadenoma mammae in the world. The study was conducted in Padang from August - September 2021 with the design used was Case Control with a total sample of 94 respondents divided into two groups, namely 47 respondents in the case group experiencing Fibroadenoma mammae and 47 respondents in the control group not experiencing Fibroadenoma mammae. The data used were primary data and secondary data. Data were presented univariately and bivariately by using the chi-square test. The results showed that there was a significant relation between age at menarche with p value = 0.013 (p < 0.05) and OR = 4.336, family history p value = 0.036 (p < 0.05) and OR = 2.679 and lifestyle p = 0.007 (p < 0.05). 0.05) and OR = 3.531 with the incidence of Fibroadenoma mammae. The conclusion of this study is that there was a relation among age at menarche, family history, and lifestyle with the incidence of Fibroadenoma mammae. It is suggested that adolescents should pay more attention to their lifestyle, especially those related to the triggers of Fibroadenoma mammae.. 05) and OR = 2.679 and lifestyle p = 0.007 (p < 0.05). 0.05) and OR = 3.531 with the incidence of Fibroadenoma mammae. The conclusion of this study is that there was a relation among age at menarche, family history, and lifestyle with the incidence of Fibroadenoma mammae. It is suggested that adolescents should pay more attention to their lifestyle, especially those related to the triggers of Fibroadenoma mammae.. 05) and OR = 2.679 and lifestyle p = 0.007 (p < 0.05). 0.05) and OR = 3.531 with the incidence of Fibroadenoma mammae. The conclusion of this study is that there was a relation among age at menarche, family history, and lifestyle with the incidence of Fibroadenoma mammae. It is suggested that adolescents should pay more attention to their lifestyle, especially those related to the triggers of Fibroadenoma mammae..